PELAKSANAAN PEMBELAJARAN MENULIS TEKS PANTUN PADA SISWA KELAS VII SMPN 3 KOTA BENGKULU TAHUN PELAJARAN 2016/2017 - Dewi Wulandari; Susetyo Susetyo; Amrizal Amrizal (Universitas Bengkulu, 2017)
The purpose of this study describes the implementation of textbook writing pantun students and the implementation of text ratings pantun works of students of class VII 2 SMPN 3 Kota Bengkulu. The method used in this research is descriptive qualitative method. The subject of this research is the teacher who is carrying out the learning and the students who are following the pantun text writing lesson in class VII 2 SMPN 3 Kota Bengkulu. Data collection techniques used observation, interviews, and document studies. Data analysis techniques used are Miles and Huberman which include data reduction, data presentation, data verification, and conclusion. Test data validity used is source triangulation. The results showed that the implementation of pantun text writing lesson in class VII 2 using scientific approach and implemented based on the Implementation Plan of Learning that has been made by the teacher. Teachers carry out the assessment of the text of the students 'pantun begins by giving instructions on performing the task of writing the pantun, the students doing the tasks and collecting the task, the teacher reading and assessing the students' pantun based on the assessment criteria contained in the Lesson Plan. Based on the assessment, the grade averaged 76.5.